2019
DOI: 10.1007/s00253-019-09888-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metabolite accumulation on the structure, viability and development of succinic acid–producing biofilms of Actinobacillus succinogenes

Abstract: Biofilms of Actinobacillus succinogenes have demonstrated exceptional capabilities as biocatalysts for high productivity, titre, and yield production of succinic acid (SA). The paper presents a microscopic analysis of A. succinogenes biofilms developed under varied fermenter conditions. The concentration of excretion metabolites is controlled by operating the fermenter in a continuous mode where the liquid throughput is adjusted. It is clearly illustrated how the accumulation of excreted metabolites (concomita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In addition, the in vitro addition of SA promoted the formation of H 2 S and biofilms in cocultured strains. Mokwatlo et al showed that SA contributed to the formation of biofilms, and stable biofilms in turn promoted the production of more SA by bacteria . In addition, the formation of cell wall biosynthesis also contributes to biofilm biosynthesis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the in vitro addition of SA promoted the formation of H 2 S and biofilms in cocultured strains. Mokwatlo et al showed that SA contributed to the formation of biofilms, and stable biofilms in turn promoted the production of more SA by bacteria . In addition, the formation of cell wall biosynthesis also contributes to biofilm biosynthesis .…”
Section: Discussionmentioning
confidence: 99%
“…Mokwatlo et al showed that SA contributed to the formation of biofilms, and stable biofilms in turn promoted the production of more SA by bacteria. 45 In addition, the formation of cell wall biosynthesis also contributes to biofilm biosynthesis. 46 Similarly, in our study, the cell wall biosynthesis metabolic pathway in the A11 strain was upregulated in the coculture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, succinate had an important inhibitory effect on cell growth as well as on SA production; to our knowledge, this observation was not widely reported. Cells growth was suitable for inhibition detection caused by SA production [72]. The results obtained from inhibition tests carried out on different Petri dishes showed negative growth starting from 0.4 mol L −1 of SA concentration.…”
Section: Effect Of Sa On Bacterial Growthmentioning
confidence: 99%
“…Two types of bioreactors were used in the study. The first bioreactor (bioreactor A) was custom developed by this research group for the purpose of microscopic visualisation of biofilm development; the details of this reactor was presented in Mokwatlo et al [16]. The visualisation and analysis of the microscopic biofilm development was facilitated by the extraction of multiple asynchronous sterile samples of biofilm coupons from the bioreactor volume.…”
Section: Bioreactorsmentioning
confidence: 99%
“…Various studies on biofilms have shown that hydrodynamic shear conditions and the specific growth rate of biofilms, among other factors, greatly influence the formation of biofilms, particularly their structure, stability, and the activity of cells embedded in them [13][14][15]. A previous study, by this research group, investigated the influence of acid accumulation on the development, structure, and viability of A. succinogenes biofilms [16]. This study found that high acid conditions (above 10 g L −1 SA) impeded biofilm growth and resulted in patchy biofilms with significant cell death, whereas low acid conditions (below 10 g L −1 SA) favoured biofilm growth with relatively higher cell viability within biofilms.…”
Section: Introductionmentioning
confidence: 99%